A Two-Phased Gradient Technique For Budget Allocation: An Application To Data Collection Budget Allocation In Efficiency Measurement Of DEA. - Wai, Peng Wong; Loo, Hay Lee; Jaruphongsa, Wikrom (2010)

(untitled)
This paper presents a gradient based algorithm to solve the data collection budget allocation problem in efficiency measurement of DEA.